2010
DOI: 10.1371/journal.pone.0009056
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Genes and Putative Biomarker Identification Using Distribution Metrics on Expression Profiles

Abstract: BackgroundIdentification of genes with switch-like properties will facilitate discovery of regulatory mechanisms that underlie these properties, and will provide knowledge for the appropriate application of Boolean networks in gene regulatory models. As switch-like behavior is likely associated with tissue-specific expression, these gene products are expected to be plausible candidates as tissue-specific biomarkers.Methodology/Principal FindingsIn a systematic classification of genes and search for biomarkers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…A surprising and striking observation from our time-course data was that many of the major signaling pathways (e.g., MAPK, calcium, and p53 signaling, as well as apoptosis) altered in late-stage HF displayed a biphasic course with changes in the completely opposite direction earlier in the course of disease. Results obtained from human and mouse data affirm that genes with a switch-like or bimodal expression play a large role in cell communication and are enriched for functions in extracellular and intercellular signal transduction (9,13). To our knowledge, extensive bidirectional transcriptional regulation in HF has not been previously appreciated.…”
Section: Discussionmentioning
confidence: 72%
“…A surprising and striking observation from our time-course data was that many of the major signaling pathways (e.g., MAPK, calcium, and p53 signaling, as well as apoptosis) altered in late-stage HF displayed a biphasic course with changes in the completely opposite direction earlier in the course of disease. Results obtained from human and mouse data affirm that genes with a switch-like or bimodal expression play a large role in cell communication and are enriched for functions in extracellular and intercellular signal transduction (9,13). To our knowledge, extensive bidirectional transcriptional regulation in HF has not been previously appreciated.…”
Section: Discussionmentioning
confidence: 72%
“…This study suggests a complementary strategy, whereby we first identified those transcripts that showed bimodal expression levels, and then identified the polymorphism responsible for this differential expression. Clustering methods [ 6 ] and statistical methods [ 7 , 10 , 33 ] have previously been used to identify bimodal expression in large datasets. These methods have the advantage of being motivated by strong theoretical statistical considerations.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have the advantage of being motivated by strong theoretical statistical considerations. However, they also require a moderate level of statistical understanding, and in addition some of these methods can only be easily applied to large-scale meta-analysis of several data sets [ 10 ] and may be less suitable for small expression data sets generated in a single laboratory. The approach we suggest is able to be used alongside more complex approaches by laboratory scientists with only basic statistical training, who are in a good position to immediately follow up their results experimentally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation